Nephrolithiasis Treatment Costs among Patients at a Vietnamese Public Hospital - Dinh Pham, Dr. Luyen (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Nephrolithiasis has been rising in prevalence worldwide, imposing a significant cost burden on both patients and society in general. Desmodium styracifolium extract (DSE) and Rowatinex® are the two stone-eroding pharmaceuticals most commonly used to treat nephrolithiasis in Vietnam. This study aimed to compare the treatment costs and durations between Rowatinex® and DSE in Vietnamese patients with nephrolithiasis. Materials and Methods: This was a retrospective cost-of-illness analysis of the information extracted from a public hospital’s electronic database. This study was based on the prevalence approach, and it focused on the health-care provider perspective. All ambulatory patients who were diagnosed with nephrolithiasis from January 2015 to December 2017 were filtered using specific inclusion and exclusion criteria. Results and Discussion: A total of 1,001 patients who were prescribed Rowatinex® and 882 patients who were prescribed DSE were included in this research. The majority were 30–59 years old and had no health insurance. The pharmaceutical expenses accounted for the highest percentage of the total cost (59.8% for Rowatinex® and 67.9% for DSE). Overall, the Rowatinex® treatment had a higher average cost per patient than the DSE (290.5 vs. 264.3 US dollars); however, it was used over a shorter duration of time (10.8 weeks vs. 19.6 weeks). Conclusion: Based on the results of this study, Rowatinex® is a more ideal choice for patients with kidney stone disease.